2012
DOI: 10.1177/0196859912466411
|View full text |Cite
|
Sign up to set email alerts
|

David, Goliath, and the Black Panthers

Abstract: Both the Hebrew Bible and the Qur'an tell the story of David and Goliath, in which David, a youth armed only with stones and a sword, challenges and kills the giant Goliath, thus securing the victory of the Israelites over the Philistines. The event was a military victory; it also created and secured the identity of a people with a sense of its own power. Today the phrase "David and Goliath" is used as shorthand to refer to a situation in which a smaller or significantly weaker force defeats a larger and much … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…If, during the civil rights movement, violent outbreaks slightly increased the public perception of grievances as legitimate (Baggetta & Myers, 2022), research on recent mass movements has demonstrated that violent protests could also cause a drop in public support (Muñoz & Anduiza, 2019) or increase public opinion in favour of the movement’s repression (Metcalfe & Pickett, 2022). In fact, violent protests often result in unpredictable, if not damaging, media interpretations of social movements (Gatchet & Cloud, 2013). For instance, scholars have shown that the dominant media were likely to frame these violent episodes as senseless (Juris, 2005), while governments depoliticized the use of violence by protesters through mobilizing a rhetoric around the term “riots” (Murphy, 2011; Tilly, 2003).…”
Section: Researching the Intersection Of Violence And Resistancementioning
confidence: 99%
“…If, during the civil rights movement, violent outbreaks slightly increased the public perception of grievances as legitimate (Baggetta & Myers, 2022), research on recent mass movements has demonstrated that violent protests could also cause a drop in public support (Muñoz & Anduiza, 2019) or increase public opinion in favour of the movement’s repression (Metcalfe & Pickett, 2022). In fact, violent protests often result in unpredictable, if not damaging, media interpretations of social movements (Gatchet & Cloud, 2013). For instance, scholars have shown that the dominant media were likely to frame these violent episodes as senseless (Juris, 2005), while governments depoliticized the use of violence by protesters through mobilizing a rhetoric around the term “riots” (Murphy, 2011; Tilly, 2003).…”
Section: Researching the Intersection Of Violence And Resistancementioning
confidence: 99%
“…The idea that the rhetoric of subordinate groups can be useful in the process of world making is not new. Gatchet and Cloud (2012, pp. 5-7) argue that the position of perceived weakness can provide rhetorical and material opportunities for those facing oppression.…”
mentioning
confidence: 99%